Midwives providing woman-centred care during the COVID-19 pandemic in Australia: A national qualitative study. Issue 5 (September 2022) - Stulz, Virginia M.; Bradfield, Zoe; Cummins, Allison; Catling, Christine; Sweet, Linda; McInnes, Rhona; McLaughlin, Karen; Taylor, Jan; Hartz, Donna; Sheehan, Athena
Abstract: Background: The COVID-19 pandemic has caused isolation, fear, and impacted on maternal healthcare provision. Aim: To explore midwives' experiences about how COVID-19 impacted their ability to provide woman-centred care, and what lessons they have learnt as a result of the mandated government and hospital restrictions (such as social distancing) during the care of the woman and her family. Methods: A qualitative interpretive descriptive study was conducted. Twenty-six midwives working in all models of care in all states and territories of Australia were recruited through social media, and selected using a maximum variation sampling approach. Data were collected through in-depth interviews between May to August, 2020. The interviews were recorded, transcribed verbatim, and thematically analysed. Findings: Two overarching themes were identified: 'COVID-19 causing chaos' and 'keeping the woman at the centre of care'. The 'COVID-19 causing chaos' theme included three sub-themes: 'quickly evolving situation', 'challenging to provide care', and 'affecting women and families'. The 'Keeping the woman at the centre of care' theme included three sub-themes: 'trying to keep it normal', 'bending the rules and pushing the boundaries', and 'quality time for the woman, baby, and family unit'. Conclusion: Findings of this study offer important evidence regarding the impact of the pandemic on the provision of woman-centred care which is key to midwifery philosophy. Recommendations are made for ways to preserve and further enhance woman-centred care during periods of uncertainty such as during a pandemic or other health crises.